The efficacy of the seamless transfer of care model to apply for the patients with cerebral apoplexy in China - Wei Xie; Zhen-Hua Zhao; Qing-Min Yang; Fang-Hong Wei (Elsevier, 2015)
Purpose: To evaluate the efficacy of the Seamless Transfer of Care Model (STCM) to improve readmission occurrence of patients withstroke. Methods: The sample was comprised of fifty-nine subjects with stroke who were hospitalized in the geriatric and neurology departments of a large university hospital in China. Subjects were allocated to an STCM group (n = 30) or a routine care (control) group (n = 29). Results: Compared with the control group, the STCM group had a higher quality of life (p < 0.05), higher compliance (p < 0.05) and a lower readmission rate (p < 0.05). Conclusion: Based on our results, the application of the STCM in Chinese stroke patients can improve quality of life and compliance, and reduce readmission rate.